The Value of Character Education in the Novel Matahari by Tere Liye and Relevensi as Literary Learning in High School - Rosyada, Amrina; Kundharu Saddhono; Nugraheni Eko Wardani (Jurnal Sastra Indonesia, 2025)
Morality is part of the elements of structured cultural values. This study aims to describe the value of character education in the novel Matahari by Tere Liye as the relevance of literary learning in high school. This type of research uses a qualitative description with a content analysis approach. The data in the study is in the form of quotes of words, sentences, and paragraphs in the novel. The data source was obtained through Tere Liye's novel Matahari. The data collection technique in this study is document analysis that reflects the character values of Pancasila student profiles integrated through Lickona's theory. Data analysis techniques include reading, analysis, and recording. The data validity test was conducted through theoretical triangulation using the following analysis techniques. The results of this study reveal that the values of character education in the novel Matahari by Tere Liye reflect the value of character education of Pancasila student profiles, The values of character education are then integrated into the theory put forward by Lickona by covering three main dimensions; moral knowing, moral feeling, and moral action. In addition, the findings in this study also reveal that the character education values contained in the novel not only represent the ethical aspect but also reflect cultural values that are relevant to the context of character education in schools.